2012
DOI: 10.1614/ws-d-11-00196.1
|View full text |Cite
|
Sign up to set email alerts
|

Local Conditions, Not Regional Gradients, Drive Demographic Variation of Giant Ragweed (Ambrosia trifida) and Common Sunflower (Helianthus annuus) Across Northern U.S. Maize Belt

Abstract: Knowledge of environmental factors influencing demography of weed species will improve understanding of current and future weed invasions. The objective of this study was to quantify regional-scale variation in vital rates of giant ragweed and common sunflower . To accomplish this objective, a common field experiment was conducted across seven sites between 2006 and 2008 throughout the north central U.S. maize belt. Demographic parameters of both weed species were measured in intra-and interspecific competitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 49 publications
3
22
0
Order By: Relevance
“…Variation in plant size of A. artemisiifolia was previously found in field surveys in smaller geographical areas (Fumanal et al 2007a(Fumanal et al , 2008Ortmans et al 2016), but our study shows that variation across sites (rather than across regions) is also the most important spatial level when examined across the entire European distribution of the species. Local conditions and not regional gradients were also found to drive demographic variation in two closely related species, Ambrosia trifida and Helianthus annuus, on corn fields in the US (Wortman et al 2012). Spatial variation in plant volume of A. artemisiifolia was best explained, however, by combining explanatory information from all levels (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…Variation in plant size of A. artemisiifolia was previously found in field surveys in smaller geographical areas (Fumanal et al 2007a(Fumanal et al , 2008Ortmans et al 2016), but our study shows that variation across sites (rather than across regions) is also the most important spatial level when examined across the entire European distribution of the species. Local conditions and not regional gradients were also found to drive demographic variation in two closely related species, Ambrosia trifida and Helianthus annuus, on corn fields in the US (Wortman et al 2012). Spatial variation in plant volume of A. artemisiifolia was best explained, however, by combining explanatory information from all levels (i.e.…”
Section: Discussionmentioning
confidence: 95%
“…We set the rate of giant ragweed seedling emergence from the soil seed bank at 18%, based on the findings of Harrison et al [22]. This value lies well within the range (6% to 45%) reported by Wortman et al [43] for giant ragweed seedling emergence across 34 site-year combinations in the north-central U.S. We did not use crop-specific seedling emergence rates, as Goplen et al [23] had reported no differences in giant ragweed emergence among different crops in the first year after seed deposition.…”
Section: Giant Ragweed Demographic Parametersmentioning
confidence: 88%
“…Unfortunately, detailed information about irrigation management was rarely reported and these effects could not be explored in this meta-analysis. It is also important to note that climate and geographical clines are not always effective predictors of plant response and yield in short-term studies due to the potential for irregular weather events at a given site-year (Wortman et al, 2012b). However, observed annual precipitation and soil temperature (potentially useful and predictive weather variables in this meta-analysis) were not reported in most studies.…”
Section: Climatic Influence On Yield Responsementioning
confidence: 94%